Triazacoronene‐Based 2D Conductive Metal–Organic Framework for High‐Capacity Lithium Storage - Yin, Jia‐Cheng; Lian, Xin; Li, Zhi‐Gang; Cheng, Mingren; Liu, Ming; Xu, Jian; Li, Wei; Xu, Yunhua; Li, Na; Bu, Xian‐He (Advanced functional materials, 2024)
2D conductive metal–organic frameworks (2D c‐MOFs) have attracted increasing attention as promising electrode materials for rechargeable batteries due to their designable periodic motifs, large specific surface areas, and prominent electrical conductivity. However, the development of 2D c‐MOF electrode materials with functionality remains a significant challenge because of the limited electroactive ligand motifs available. Herein, a hexahydroxy‐substituted triazacoronene ligand (6OH‐TAC) is deliberately designed and synthesized, which coordinates with Cu2+ ions to form an unprecedented 2D c‐MOF (Cu‐TAC) with functionality sites of efficient lithium storage. The synergistic effect of TAC and CuO4 enables Cu‐TAC as an anode for lithium‐ion batteries with a superior reversible capacity of 772.4 mAh g−1 at 300 mA g−1, remarkable rate performance, and outstanding long‐term cyclability (83% capacity retention at 300 mA g−1 for 600 cycles). These metrics outperform almost all 2D c‐MOF‐based electrodes, shedding light on new opportunities for energy storage devices. A new 2D conductive metal–organic framework (2D c‐MOF, Cu‐TAC) is synthesized via the coordination of a novel hexahydroxy‐substituted triazacoronene (6OH‐TAC) ligand with Cu2+ ions. The Cu‐TAC exhibits prominent lithium storage capability in lithium‐ion batteries with an exceptionally high reversible capacity, remarkable rate performance, and long‐term cycling stability due to its good conductivity, abundant active sites, and excellent stability.